An Approximation Method for Solving Volterra Integrodifferential Equations with a Weighted Integral Condition. (12th May 2015) - Guezane-Lakoud, A.; Bendjazia, N.; Khaldi, R.
Abstract : We apply the reproducing kernel Hilbert space (RKHS) method for getting analytical and approximate solutions for second-order hyperbolic integrodifferential equations with a weighted integral condition. The analytical solution is represented in the form of series; thus, the n -terms approximate solutions are obtained. The results of the numerical examples are compared with the exact solutions to illustrate the accuracy and the effectivity of this method.